2011
DOI: 10.1371/journal.pgen.1002072
|View full text |Cite
|
Sign up to set email alerts
|

Nodal-Dependent Mesendoderm Specification Requires the Combinatorial Activities of FoxH1 and Eomesodermin

Abstract: Vertebrate mesendoderm specification requires the Nodal signaling pathway and its transcriptional effector FoxH1. However, loss of FoxH1 in several species does not reliably cause the full range of loss-of-Nodal phenotypes, indicating that Nodal signals through additional transcription factors during early development. We investigated the FoxH1-dependent and -independent roles of Nodal signaling during mesendoderm patterning using a novel recessive zebrafish FoxH1 mutation called midway, which produces a C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 84 publications
7
69
0
1
Order By: Relevance
“…Importantly, in zebrafish, loss of both Foxh1 and Mixer resulted in a phenotype consistent with a substantial reduction of Nodal activity (Kunwar et al 2003). Complete loss of Nodal signaling in zebrafish, however, results in a more severe phenotype, suggesting that additional Smad2-recruiting transcription factors exist (Kunwar et al 2003;Slagle et al 2011).…”
Section: Smad-interacting Transcription Factorsmentioning
confidence: 92%
“…Importantly, in zebrafish, loss of both Foxh1 and Mixer resulted in a phenotype consistent with a substantial reduction of Nodal activity (Kunwar et al 2003). Complete loss of Nodal signaling in zebrafish, however, results in a more severe phenotype, suggesting that additional Smad2-recruiting transcription factors exist (Kunwar et al 2003;Slagle et al 2011).…”
Section: Smad-interacting Transcription Factorsmentioning
confidence: 92%
“…S11). Eomes, a T-box protein, binds Smad2 and has been implicated in Nodal-mediated mesendoderm induction in Xenopus, zebrafish and mammalian epiblast stem cells (Arnold et al, 2008;Picozzi et al, 2009;Slagle et al, 2011;Teo et al, 2011). Recently, ChIP-seq analysis of Eomes has been reported in Xenopus (Gentsch et al, 2013), allowing for a direct test of whether both Smad2/3 and Eomes are bound to the aforementioned 15 genes.…”
Section: Tgfβ Signaling and Smad Partner Proteinsmentioning
confidence: 99%
“…In mouse, Foxh1 −/− embryos display a spectrum of phenotypes from severe gastrulation defects to milder anterior and midline deficiencies (Hoodless et al, 2001;Yamamoto et al, 2001). In zebrafish, schmalspur and midway mutants, both defective in the foxh1 gene, are deficient in prechordal plate, notochord and some axial mesoderm development (Pogoda et al, 2000;Sirotkin et al, 2000;Slagle et al, 2011). Loss of Foxh1 in Xenopus laevis results in reduced expression of mesendodermal markers, including gsc, nodal1 and mix1, but axial mesoderm was still present, albeit obviously abnormal (Howell et al, 2002;Kofron et al, 2004b;Watanabe and Whitman, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while the presence of consensus FoxH1-binding sites may generally be suggestive of Nodal-dependent regulation, FoxH1 is not the sole effector for Nodal-dependent functions in zebrafish. A recent report identified the Tbox protein Eomesodermin (Ryan et al, 1996) as an additional mediator of Nodal-dependent functions in the zebrafish (Slagle et al, 2011). In this study, inhibition of both FoxH1 and Eomesodermin function was found to recapitulate the phenotype observed upon complete inhibition of Nodal signaling.…”
Section: Developmental Dynamicsmentioning
confidence: 50%